Scorpion venom as a molecular treasure: emerging bioactive compounds and translational therapeutic insights - Ritu Dahiya; Kanika Goyal; Kalicharan Sharma; Aruna Rawat; Vinita Sharma; Pooja Mathur (Archives of Toxicology, 2026)

Effect of graphene-based paraffin composite on performance enhancement of IoT-integrated box-type solar cooker - Amit Tiwari; Ritu Jain; Harshita Swarnkar; Payal Bansal; Manas Mathur; Himanshu Vasnani (Environmental Science and Pollution Research, 2025)

Hesperetin-supplemented soybean and ginger hydroalcoholic extracts alleviate diabetic cardiomyopathy in streptozotocin induced diabetic rats by modulating NF-κB/MMP-9/TIMPs pathway - Ritu; Ravinder Verma; Sudhir Kaushik; Prabhnain Kaur; Pooja Mathur; T. Velpandian; Ramesh K Goyal (South African Journal of Botany, 2025)

Synergistic effect of pyrene and heavy metals (Zn, Pb, and Cd) on phytoremediation potential of Medicago sativa L. (alfalfa) in multi-contaminated soil - Jyoti Mathur; Ritu Panwar (Environmental Science and Pollution Research, 2024)

Remediation of polycyclic aromatic hydrocarbon-contaminated soils using microbes and nanoparticles: A review - Ritu PANWAR; Jyoti MATHUR (Pedosphere, 2023)

Enhancing survival and multiplication of Trichoderma harzianum by Prosopis juliflora based compost in Indian arid region - Ritu Mawar; Tanu Mathur (Indian Phytopathology, 2022)

India’s energy sector choices—options and implications of ambitious mitigation efforts - Ritu Mathur; Swapnil Shekhar (Climatic Change, 2020)

Leaf nutrient dynamics of shrubs in a tropical dry deciduous forest in Rajasthan in North-West India - Vivek Mishra; Atar Singh Yadav; Ritu Mathur (Tropical Ecology, 2020)

A new scenario framework for climate change research: the concept of shared socioeconomic pathways - Brian C. O’Neill; Elmar Kriegler; Keywan Riahi; Kristie L. Ebi; Stephane Hallegatte; Timothy R. Carter; Ritu Mathur; Detlef P. van Vuuren (Climatic Change, 2014)

A new scenario framework for Climate Change Research: scenario matrix architecture - Detlef P. van Vuuren; Elmar Kriegler; Brian C. O’Neill; Kristie L. Ebi; Keywan Riahi; Timothy R. Carter; Jae Edmonds; Stephane Hallegatte; Tom Kram; Ritu Mathur; Harald Winkler (Climatic Change, 2014)
This paper describes the scenario matrix architecture that underlies a framework for developing new scenarios for climate change research. The matrix architecture facilitates addressing key questions related to current climate research and policy-making: identifying the effectiveness of different adaptation and mitigation strategies (in terms of their costs, risks and other consequences) and the possible trade-offs and synergies. The two main axes of the matrix are: 1) the level of radiative forcing of the climate system (as characterised by the representative concentration pathways) and 2) a set of alternative plausible trajectories of future global development (described as shared socio-economic pathways). The matrix can be used to guide scenario development at different scales. It can also be used as a heuristic tool for classifying new and existing scenarios for assessment. Key elements of the architecture, in particular the shared socio-economic pathways and shared policy assumptions (devices for incorporating explicit mitigation and adaptation policies), are elaborated in other papers in this special issue.

A new scenario framework for climate change research: background, process, and future directions - Kristie L. Ebi; Stephane Hallegatte; Tom Kram; Nigel W. Arnell; Timothy R. Carter; Jae Edmonds; Elmar Kriegler; Ritu Mathur; Brian C. O’Neill; Keywan Riahi; Harald Winkler; Detlef P. Van Vuuren; et al. (Climatic Change, 2014)
The scientific community is developing new global, regional, and sectoral scenarios to facilitate interdisciplinary research and assessment to explore the range of possible future climates and related physical changes that could pose risks to human and natural systems; how these changes could interact with social, economic, and environmental development pathways; the degree to which mitigation and adaptation policies can avoid and reduce risks; the costs and benefits of various policy mixes; and the relationship of future climate change adaptation and mitigation policy responses with sustainable development. This paper provides the background to and process of developing the conceptual framework for these scenarios, as described in the three subsequent papers in this Special Issue (Van Vuuren et al., 2013; O’Neill et al., 2013; Kriegler et al., Submitted for publication in this special issue). The paper also discusses research needs to further develop, apply, and revise this framework in an iterative and open-ended process. A key goal of the framework design and its future development is to facilitate the collaboration of climate change researchers from a broad range of perspectives and disciplines to develop policy- and decision-relevant scenarios and explore the challenges and opportunities human and natural systems could face with additional climate change.

On –farm waste-based composts in managing Macrophomina phaseolina induced dry root rot of guar in an arid environment - Meenu Bareja; Ritu Mawar; Manish Mathur; Satish Lodha (Australasian Plant Pathology, 2013)